Preventing Re-Emergence of COVID-19: A National Survey of Public Risk Perceptions and Behavioural Intentions Concerning Travel Plan Among Taiwanese - Wong, Li Ping; Chiu, Ching-Ju; Alias, Haridah; Lee, Tony Szu-Hsien; Hu, Zhijian; Lin, Yulan (Frontiers in Public Health, 2021)
Background The objectives of this study were to investigate risk perceptions and travel intention among the general public in Taiwan during the COVID-19 outbreak. Methods A cross-sectional, Web-based anonymous survey using an online questionnaire disseminate to the general public using LINE and Facebook. Results A total of 3,237 complete responses were received, of whom 5.8% (95% CI 5.1−6.7) of the participants reported intent to travel to overseas countries with an apparent community spread and 5.5% (95% CI 4.7−6.3) reported intent to travel to other overseas countries in the next one month. A relatively higher proportion (46.5%; 95% CI 44.7−48.2) reported intention for domestic travelling. Participants who viewed travelling to only be risky for older adults or those with medical conditions (OR=2.19; 95% CI 1.38−3.47) and who perceived that one will not get infected if one takes recommended precautionary measures (OR=3.12; 95% CI 1.85−5.27) reported higher travelling intention to overseas countries with an apparent community spread. Conclusions Overall, the findings suggest that risk perceptions were depicted as a strong influence of travel intentions.